Macular Microvasculature Is Different in Patients with Primary Sjögren’s Disease Compared to Healthy Controls - Gyde Tadsen; Nadine Zehrfeld; Laura Hoffmann; Marten Gehlhaar; Bettina Hohberger; Christian Mardin; Torsten Witte; Carsten Framme; Diana Ernst; Katerina Hufendiek (Diagnostics, 2025)
Background/Objectives: This study investigates the macular microvasculature in a large cohort of primary Sjögren’s disease (SjD) patients using optical coherence tomography angiography (OCTA), focusing on how disease duration, activity, and hydroxychloroquine (HCQ) treatment influence retinal microcirculation. Methods: A total of 106 eyes (53 SjD patients) and 70 eyes (35 age- and gender-matched healthy controls (HCs)) were examined. The vessel area density (VAD, %) and foveal avascular zone (FAZ, mm2) were measured in three retinal layers: Superficial Vascular Plexus (SVP), Intermediate Capillary Plexus (ICP), and Deep Capillary Plexus (DCP), respectively, in three peri-macular circular sectors (c1, c2, c3) each. Results: The VAD was significantly lower in c1 of the DCP in SjD compared to HCs (29.14 ± 7.07 vs. 31.78 ± 9.55, p = 0.038). The FAZ was significantly larger in SjD in both SVP (0.41 ± 0.13 vs. 0.34, 0.11, p < 0.001; Cohen’s |d| = 0.55) and DCP (0.45 ± 0.15 vs. 0.4 ± 0.14, p = 0.014; Cohen’s |d| ± 0.38). Significant correlations were observed between the FAZ size and reductions in the VAD in the SVP and DCP (p = 0.010, Cohen’s |d| = 0.2; p < 0.001, Cohen’s |d| ± 0.26) and across all layers combined (p = 0.019, Cohen’s |d| = −0.18). Conclusions: There was a negative correlation between the VAD in the DCP and disease duration (ρ = −0.28, p = 0.040). No significant correlation was identified between the duration of HCQ intake and the VAD or FAZ. Our findings indicate microvascular alterations in the DCP of SjD, characterized by a reduced VAD and an enlarged FAZ, which may be attributable to inflammatory or arteriosclerotic factors. OCTA may prove to be a valuable tool for the stratification of vascular risk in SjD.